Perception of vulnerability to HPV and headand neck cancer: sexual and risk behaviors in youths from Niteríi, RJ - Silva, Igor Iuco Castro; Coutinho, Lawrence A.C.R.; Silva Júnior, José A.; Pires, Andréa R.C.; Bastos, Otílio M.P. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: the association of human papillomavirus (HPV) to squamous cell carcinoma in the region of head and neck represents a public health problem, especially to young people who are more prone to sexually transmited diseases (STD). Objective: to assess the vulnerability to transmission of HPV and head and neck cancer in young population from the city of Niteroi. Methods: an exploratory and descriptive study was conducted using questionnaires with 450 participants. The data were divided into socio-demographic characteristics, sexual behavior, risk factors for oral cancer, association between oral symptoms, oral regions and medical history and education and prevention in the context of HPV. Statistical analysis was performed using chi-squared test and considering p < 0.05. Results: in comparison to females, young males were more vulnerable to HPV due to early sexual debut, multiple sexual partners and unsafe oral sex, and to oral cancer mediated by alcohol, and lower general knowledge about HPV. In both sexes, genital warts pre-figured as the most prevalent diseases (5% of total), with association in men to the symptoms of throat and the other STD. Conclusion: the young population from Niteroi presents risky sexual behaviours such as vulnerability to HPV infection and high alcohol consumption which increase suscetibility to carcinogenesis in head and neck. There should be greater coordination of public health policies to promote educational preventive actions in the field of STD and to combat early alcohol abuse.